PERAN PENDIDIKAN ANTI KORUPSI DALAM MEMBANGUN BUDAYA POLITIK DEMOKRATIS DI KALANGAN MAHASISWA - Serlin Fitriana; Naysya Desky; Novita Sary Hasibuan; Sapta Kesuma; Muharri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Corruption is one of the fundamental problems that hinder democratic development in Indonesia. This study aims to examine the role of anti-corruption education in building a democratic political culture among university students. Using a descriptive qualitative approach and literature study, this research analyzes how the internalization of anti-corruption values such as honesty, integrity, responsibility, and transparency can encourage the formation of democratic student character. The results show that anti-corruption education significantly contributes to shaping students' political awareness, increasing democratic participation, and strengthening commitment to good governance values. The implementation of anti-corruption education through formal curricula, extracurricular activities, and campus culture has proven effective in transforming students into agents of change with integrity.